Genomic Variability of SARS-CoV-2 Omicron Variant Circulating in the Russian Federation during Early December 2021 and Late January 2022 - Ekaterina N. Chernyaeva; Andrey A. Ayginin; Irina A. Bulusheva; Kirill S. Vinogradov; Ivan F. Stetsenko; Svetlana V. Romanova; Anastasia V. Tsypkina; Alina D. Matsvay; Yulia A. Savochkina; German A. Shipulin (Pathogens, 2022)
Analysis of genomic variability of pathogens associated with heightened public health concerns is an opportunity to track transmission routes of the disease and helps to develop more effective vaccines and specific diagnostic tests. We present the findings of a detailed genomic analysis of the genomic variability of the SARS-CoV-2 Omicron variant that spread in Russia between 8 December 2021 and 30 January 2022. We performed phylogenetic analysis of Omicron viral isolates collected in Moscow (n = 589) and downloaded from GISAID (n = 397), and identified that the BA.1 lineage was predominant in Russia during this period. The BA.2 lineage was also identified early in December 2021. We identified three cases of BA.1/BA.2 coinfections and one case of Delta/Omicron coinfection. A comparative genomic analysis of SARS-CoV-2 viral variants that spread in other countries allowed us to identify possible cases of transmission. We also found that some mutations that are quite rare in the Global Omicron dataset have a higher incidence rate, and identified genetic markers that could be associated with ways of Omicron transmission in Russia. We give the genomic variability of single nucleotide variations across the genome and give a characteristic of haplotype variability of Omicron strains in both Russia and around the world, and we also identify them.